2020
DOI: 10.1002/hon.2771
|View full text |Cite
|
Sign up to set email alerts
|

Illuminating novel biological aspects and potential new therapeutic approaches for chronic myeloproliferative malignancies

Abstract: This review reflects the presentations and discussion at the 14th post-American Society of Hematology (ASH) International Workshop on Chronic Myeloproliferative Malignancies, which took place on the December 10 and 11, 2019, immediately after the 61st ASH Annual Meeting in Orlando, Florida. Rather than present a resume of the proceedings, we address some of the topical translational science research and clinically relevant topics in detail. We consider how recent studies using single-cell genomics and other mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…Li et al [ 14 ] found that the gene load of JAK2V617F mutation in patients with MPN was closely related to the severity and duration of the disease. Zhang et al [ 15 ] found that IFN- α specifically blocked the proliferation advantage of JAK2V617F mutant hematopoietic stem cells in mice, thereby preventing the development of MPN and even achieving eradication [ 16 ]. Clinical research has reported that some patients with MPN treated with IFN achieved complete hematologic and molecular biological remission [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Li et al [ 14 ] found that the gene load of JAK2V617F mutation in patients with MPN was closely related to the severity and duration of the disease. Zhang et al [ 15 ] found that IFN- α specifically blocked the proliferation advantage of JAK2V617F mutant hematopoietic stem cells in mice, thereby preventing the development of MPN and even achieving eradication [ 16 ]. Clinical research has reported that some patients with MPN treated with IFN achieved complete hematologic and molecular biological remission [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unlike Tyrosine Kinase Inhibitors (TKI) in CML, survival of patients with MF is not substantially improved by currently available JAK inhibition therapies since the possibility of appearance of unrelated clones over time [ 100 ]. Therefore, a major focus of drug developments is identifying novel targets beyond JAK inhibitors [ 101 ]. In this regard, a novel single-cell ‘‘multi-omics’’ method, including scRNA-seq, targeted single-cell mutational analysis with simultaneous scRNA-seq (TARGET-seq) and single-cell proteomics, has advanced ultimate reconstruction of tumor phylogenetic trees.…”
Section: Groundbreaking Insights Into Hsc By Single-cell Analysismentioning
confidence: 99%
“…Momelitinib and pacritinib, also type I JAK2 inhibitors, are in late stage development and anticipated to be licensed soon, in particular for patients with anemia and thrombocytopenia. 15,16 Indeed, pacritinib was licensed on 28th February 2022 by the US Food and Drug Administration (FDA) for the treatment of adult patients diagnosed with intermediate or highrisk MF with baseline platelets (50 � 10 9 /L). Momelitinib mitigates anemia by inhibiting the activin A receptor and decreasing hepcidin production; pacritinib has a nonmyelosuppressive profile and appears suitable for thrombocytopenic patients, in which the drug is currently being tested in a randomized, controlled, phase 3 study (PACIFICA).…”
Section: Targeting Immune Dysfunction In Myelofibrosismentioning
confidence: 99%
“…Preclinical studies, however, suggest cross‐resistance among type I JAK2 inhibitors. Momelitinib and pacritinib, also type I JAK2 inhibitors, are in late stage development and anticipated to be licensed soon, in particular for patients with anemia and thrombocytopenia 15,16 . Indeed, pacritinib was licensed on 28th February 2022 by the US Food and Drug Administration (FDA) for the treatment of adult patients diagnosed with intermediate or high‐risk MF with baseline platelets (50 × 10 9 /L).…”
Section: Introductionmentioning
confidence: 99%